Cost-of-illness studies: concepts, scopes, and methods - Jo, Changik (Clinical and molecular hepatology, 2014)
Liver diseases are one of the main causes of death, and their ever-increasing prevalence is threatening to cause significant damage both to individuals and society as a whole. This damage is especially serious for the economically active population in Korea. From the societal perspective, it is therefore necessary to consider the economic impacts associated with liver diseases, and identify interventions that can reduce the burden of these diseases. The cost-of-illness study is considered to be an essential evaluation technique in health care. By measuring and comparing the economic burdens of diseases to society, such studies can help health-care decision-makers to set up and prioritize health-care policies and interventions. Using economic theories, this paper introduces various study methods that are generally applicable to most disease cases for estimating the costs of illness associated with mortality, morbidity, disability, and other disease characteristics. It also presents concepts and scopes of costs along with different cost categories from different research perspectives in cost estimations. By discussing the epidemiological and economic grounds of the cost-of-illness study, the reported results represent useful information about several evaluation techniques at an advanced level, such as cost-benefit analysis, cost-effectiveness analysis, and cost-utility analysis.